Covalent Adaptable Networks: Toward Stimuli‐Responsive Dynamic Thermosets through Continuous Development and Improvements in Covalent Adaptable Networks (CANs) (Adv. Mater. 20/2020). Issue 20 (19th May 2020) - Podgórski, Maciej; Fairbanks, Benjamin D.; Kirkpatrick, Bruce E.; McBride, Matthew; Martinez, Alina; Dobson, Adam; Bongiardina, Nicholas J.; Bowman, Christopher N.
Abstract : Covalent adaptable networks (CANs) with two types of stimuli‐responsive crosslinks are illustrated by Christopher N. Bowman and co‐workers in article number 1906876 . Light‐responsive crosslinks are exposed to blue light to initiate the dynamic response. Thermally responsive crosslinks are activated by an increase in temperature. Either of the types of dynamic units can be reversibly cleaved by application of the triggering stimulus.